2021
DOI: 10.1002/advs.202101739
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin 2D Inorganic Ancient Pigment Decorated 3D‐Printing Scaffold Enables Photonic Hyperthermia of Osteosarcoma in NIR‐II Biowindow and Concurrently Augments Bone Regeneration

Abstract: Osteosarcoma (OS) is the primary malignant bone tumor. Despite therapeutic strategies including surgery, chemotherapy, and radiotherapy have been introduced into the war of fighting OS, the 5-year survival rate for patients still remains unchangeable for decades. Besides, the critical bone defects after surgery, drug-resistance and side effects also attenuate the therapeutic effects and predict poor prognosis. Recently, photothermal therapy (PTT) has attracted extensive attention featuring minimal invasiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 45 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…11h). 205 The obtained CaPCu scaffold exhibited excellent biodegradability and biocompatibility, and no obvious cytotoxicity and immunogenicity were observed. Particularly, the NIR-II-activated photothermal effect of EB nanosheets could make the CaPCu scaffold destroy the disease lesion, while exhibiting a negligible heating effect in normal surrounding tissue, promoting bone tissue regeneration (Fig.…”
Section: Mins In Tissue Engineeringmentioning
confidence: 92%
“…11h). 205 The obtained CaPCu scaffold exhibited excellent biodegradability and biocompatibility, and no obvious cytotoxicity and immunogenicity were observed. Particularly, the NIR-II-activated photothermal effect of EB nanosheets could make the CaPCu scaffold destroy the disease lesion, while exhibiting a negligible heating effect in normal surrounding tissue, promoting bone tissue regeneration (Fig.…”
Section: Mins In Tissue Engineeringmentioning
confidence: 92%
“… [ 60 ] CaPCu scaffold CaCuSi 4 O 10 nanosheets CaCO 3 and PCL PTT H&E, Masson and Goldner trichrome stained photographs showed that CaPCu scaffolds acquired more new mineralized bone components. [ 61 ] Cu-TCPP-TCP scaffolds Cu-TCPP β -TCP PTT An infusion of Cu-TCPP-TCP scaffold upregulated the osteogenic differentiation-related genes. [ 48 ] Bifunctional scaffold Therapeutic agents Scaffold material Tumor therapy method Effect of therapeutic agents on osteogenesis Ref.…”
Section: Bifunctional Scaffold For Tumor Therapy and Bone Regenerationmentioning
confidence: 99%
“…These therapeutic agents can affect osteogenic differentiation by modulating cellular signaling pathways after endocytosis [ 85 ]. Therapeutic agents include metal nanomaterials [ 61 , 62 , 68 , 73 , 81 ], carbon nanomaterials [ 47 , 64 , 65 , 73 , 86 ], BP [ 86 ], etc. In addition, the effect of thermal and magnetic stimulation on inducing osteogenic differentiation has also been included and discussed [ 69 , [87] , [88] , [89] ].…”
Section: Role Of Therapeutic Agents In Bone Regenerationmentioning
confidence: 99%
“…In particular, 3D printed scaffolds have attracted considerable attention because of their striking advantages in customizing precisely matched shapes according to the anatomical structure of the patient’s defect with the aid of CT scanning and reconstruction software [ 36 ]. Currently, scaffolds loading two or more agents with synergistic therapy have been fabricated focusing on the combination of chemotherapy [ 37 , 38 ], immunotherapy [ 39 44 ], photothermal therapy (PTT) [ 45 47 ], magnetothermal therapy [ 34 , 48 ], chemodynamic therapy (CDT) [ 49 51 ], and so on [ 52 ]. However, the composition of scaffolds with synergistic therapy is more complicated than single modality, and complex functionalization processes are required [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%